Enhancing the link between in situ conservation and use of crop wild relatives (CWR) in the SADC region to underpin regional food security and mitigate predicted adverse impact of climate change - Bioversity International; University of Birmingham; University of Mauritius; Department of Agriculture, Forestry and Fisheries; Zambia Agriculture Research Institute (2014)
The leaflet provides the short description of the project “In Situ Conservation and Use of Crop Wild Relatives in three ACP countries of the Southern African Development Community (SADC) region" (2014 – 2016) and lists project activities and partners. The project aimed to enhance the link between in situ conservation and use of crop wild relatives (CWR) in the SADC region to underpin regional food security and mitigate predicted adverse impact of climate change.